Innate Immunity in the Central Nervous System: A Missing Piece of the Autoimmune Encephalitis Puzzle? - Wesselingh, Robb; Butzkueven, Helmut; Buzzard, Katherine; Tarlinton, David; O'Brien, Terence J.; Monif, Mastura (Frontiers in Immunology, 2019)
The autoimmune encephalitides are a group of autoimmune conditions targeting the central nervous system and causing severe clinical symptoms including drug-resistant seizures, cognitive dysfunction and psychiatric disturbance. Although these disorders appear to be antibody mediated, there is increasing evidence of the involvement of the innate immune system. Infiltrating monocytes and microglial proliferation, seen in neuropathological specimens, may provide the pro-inflammatory molecules seen early in the disease and contribute to the pathogenesis of the disease through blood brain barrier breakdown, and the recruitment of effector T and B cells. Finally these pro-inflammatory molecules may drive ongoing seizure activity and contribute to structural changes resulting in the long-term neurological sequelae that can impact on ongoing patient morbidity and quality of life, providing a potential target for future translational research.